Concept mapping : a critical-thinking approach to care planning - Schuster, Pamela McHugh, 1953- 4 0 16; 5 (Philadelphia, Pennsylvania : F.A. Davis Company, 2008)
A comprehensive guide for nursing students that helps them to assess, identify, and solve patients' problems.
'Twas the night before clinical -- Gathering clinical data : the foundation for the concept care maps -- Concept care maps : grouping clinical data in a meaningful manner -- Nursing interventions : so many problems, so little time -- Nursing implementation : using concept care maps as nursing care plans at the health care agency -- Including psycho-social-cultural problems in the concept care maps -- Concept care maps as the basis of documentation and phone conversations with physicians -- After the clinical day is over : patient evaluations, self-evaluations, and grading the final concept care.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; organization & administration. -- Nursing.;Critical thinking.;Nursing.;Critical thinking.;Patient Care Planning.;Audiovisual Aids.;Concept Formation.;Nursing Process; 20; 2